ANALYSIS OF TOMATO MARKETING EFFICIENCY IN LOMBOK TIMUR DISTRICT - susanti agustina; Rizal Ahmadi (Fakultas Pertanian, Universitas Gunung Rinjani, 2021)
The tomato plant has a short life cycle, it can grow to one to three in hight. This study aims to determine the marketing channels of tomatoes in East Lombok Regency and to determine the efficiency of tomato marketing on farmers’ income in East Lombok Regency. For that, we can know how many marketing channels are in East Lombok Regency and whether the marketing channels are efficient. The study uses descriptive methods. The techniques used are survey and interview techniques. The study is conducted in Lombok east district, by taking three subdistricts as sample locations impressively sampling are Suralaga, Aikmel and Wanasaba district with consideration of the subdistrict have the largert harvest and highest production. The number of respondents was conducted quota sampling as is established by as many as 30 farmers. Whereas the approval of the responders was done by the method of snow ball. Data analysis using order line analysis and marketing efficiency analysis. Research shows that the marketing margin on channel I is Rp 3000 and the second marketing channel is 5000 in efficiency on channel I is 12.57and channel II is 44.31. Farmers share to channel I is 80% and channel II is 66.67%. So every marketing channel is efficient